Systematic Literature Review: Principal’s Leadership in Improving Teachers’ Professional Competency in Schools - Septiani, Rela (PPSDP International Journal of Education, 2025)
This study aims to analyze the role of principal leadership in improving teachers’ professional competency in schools. Using a qualitative approach, data were collected through in-depth interviews, field observations, and documentation studies. The results of the study indicate that effective principal leadership, through training strategies, supervision, and ongoing coaching, can improve teacher competence in pedagogical, professional, social, and personality aspects. These findings show that an inspirational, participatory, and collaborative leadership style significantly motivates teachers to continue developing their abilities. The novelty of this study lies in the identification of a direct relationship between the participatory leadership model and the continuous improvement of teacher competence. The contribution of this study provides a practical basis for principals in designing effective professional development programs and enriches the study of educational leadership in the context of improving the quality of learning.